Effects of triple therapy on disease burden in patients of GOLD groups C and D: results from the observational COPD cohort COSYCONET - Zader, Jennifer; Jörres, Rudolf A.; Mayer, Imke; Alter, Peter; Bals, Robert; Watz, Henrik; Mertsch, Pontus; Rabe, Klaus F.; Herth, Felix; Trudzinski, Franziska; Welte, Tobias; Kauczor, Hans-Ulrich; et al. (BMC pulmonary medicine, 2024)
Randomized controlled trials described beneficial effects of inhaled triple therapy (LABA/LAMA/ICS) in patients with chronic obstructive pulmonary disease (COPD) and high risk of exacerbations. We studied whether such effects were also detectable under continuous treatment in a retrospective observational setting.
Gesehen am 20.08.2024